A new BIST scheme for low-power and high-resolution DAC testing - Li, Hongzhi; Eckmüller, Josef; Sattler, Sebastian; Eichfeld, Herbert; Weigel, Robert (Advances in Radio Science : Kleinheubacher Berichte, 2003)
A BIST scheme for testing on chip DAC is presented in this paper. We discuss the generation of on chip testing stimuli and the measurement of digital signals with a narrow-band digital filter. We validate the scheme with software simulation and point out the possibility of ADC BIST with verified DACicus-journals.
elib2cris::1512001600,li2003